PERANCANGAN SISTEM PENILAIAN KINERJA OPERATOR DENGAN METODE ANALYTIC HIERARCY PROCESS, RATING SCALE, DAN FUZZY LOGIC - Aries Susanty; Afina Fauziyyah (Universitas Mercu Buana, 2014)
Abstract: Currently, PT. Indonesia Nan Ya Indah Plastics Corporation (PT. INNAN) have not implemented the performance appraisal system to evaluate their employee‘s performance. In this time, PT. INNAN only use the level of attendance and subjective views of each section head to evaluate the performance of each employee. This condition causes the PT INNAN experiencing difficulties when PT. INNAN doing an annual evaluation in order to provide wage increases for competent‘s employees. To overcome these problems, this research aims to design a performance appraisal in accordance with the conditions of the company. The method used for the design of the performance appraisal are analytic hierarchy process (AHP), rating scale, dan fuzzy logic. There are 5 criteria and 16 sub-criteria are used as a criterion in the design of performance appraisal in the PT. INNAN. The five criteria are weighted by using AHP. Results calculated by AHP shows that the criteria which have the greatest weight is the personality, followed by discipline, skills, interpersonal, and knowledge. Furthermore, the results of the performance appraisal design tested to 10 operators in the Department of Production (Machine Calender A002) and the assessor is Division Head of Sheet. Result of assessment show us that there were two operators who have the same high value and there were one operator who have the lowest value.Keywords: Performance Appraisal of Employee, Fuzzy Logic, Rating Scale,Analytical Hierarchy Process